Pengaruh Metode Latihan Dan Power Tungkai Terhadap Tendangan Ke Gawang Jarak 16 Meter Sepak Bola - Satria Armanjaya; Ahmad Nuruhudin; Ziko Fajar Ramadhan; Aditya Trinanda (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2023)
Research Objectives: To analyze the effect of fixed target training methods and changing target training on the accuracy of kicks on soccer goals. Analyzing the influence of high power and low power on the accuracy of kicks on soccer goals. Analyzing the interaction between training methods and power on the accuracy of kicks on soccer goals on SSB Pringsewu Football School players. Research Methods Experiment with 2 x 2 factorial design. The factorial design involves two factors as independent variables, namely exercise method and leg power. The population of this study were 24 SSB Pringsewu Football School players aged 13 years. The results of the study showed that the results of the training method (fixed targets and changing targets) were 0.035 (<0.05). So there is an influence between fixed target training methods and changing target training on the accuracy of kicks at goal. The sig value for leg power (high and low) was 0.017 (<0.05). So there is an influence between high power and low power on the accuracy of kicks on soccer goals for SSB Pringsewu Football School players. The sig value for Training Method * Power is 0.000 (<0.05). In conclusion, the target training method has changed, resulting in significantly better shot accuracy on goal. High leg power is significantly better than low power. There is an interaction between training methods and power on the accuracy of kicks on goal by SSB Pringsewu Football School players.